Adsorption Characteristics of Coal-Based Activated Carbons. 1. Adsorption of Nitrogen and Carbon Dioxide - Th. El-Nabarawy; N.Sh. Petro; S.Abd. El-Aziz (Adsorption Science & Technology)
Non-activated carbon from coal contains ultrafine pores in which adsorption of nitrogen at 77 K is controlled by activated diffusion. Carbons activated with phosphoric acid or with steam contain a large fraction of microporosity. However, they do not contain ultrafine pores or pore constrictions in which activated diffusion takes place. The BET equation can be applied to calculate the surface area of microporous carbon when the monolayer capacity lies in the relative pressure range 0.05–0.30, the BET areas in such cases being comparable with those obtained from the α s -method. The Dubinin–Radushkevich (D–R) equation is the most suitable for the interpretation of CO 2 adsorption at 298 K. Chemical and physical activation starts with new pore creation, further activation being associated with pore widening. Microporosity is more predominant in chemically-activated carbons.